Planning Curriculum Development and Implementation - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Working with districts over the past 15 years to write and implement a balanced curriculum has been a wonderful experience; especially as so many of the districts that I worked with saw their student achievement improve (Squires, 2013). Now, thousands of students are getting better results because the curriculum was developed and well implemented using the Balanced Curriculum model. As is evident by the chapters about other school districts, the balanced curriculum is not the only way to get improvement, as the districts highlighted in this book also used curriculum as a framework for improving achievement. In this chapter I will highlight lessons learned along the way about developing and implementing curriculum. Using ideas described in chapter 6, we will highlight what major roles need to know and be able to do in planning, developing and implementing curriculum. For those with experience of working within a district, this will give one model to compare your district's curriculum writing and implementation efforts. We begin by dividing the effort into three areas: planning, writing, and implementing curriculum. To plan, we create a planning team to guide the process of writing and implementing curriculum. We don't separate curriculum writing from curriculum implementation because how the curriculum is implemented will, in part, depend on how the curriculum was written. We believe that such curriculum development and implementation has the potential to last over several years, and we believe that such an effort needs people who can stay the course over those years, so the effort is not wasted. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl